Contributions of Root WSC during Grain Filling in Wheat under Drought - Zhang, Jingjuan; Dell, Bernard; Ma, Wujun; Vergauwen, Rudy; Zhang, Xinmin; Oteri, Tina; Foreman, Andrew; Laird, Damian; Van den Ende, Wim (Frontiers in Plant Science, 2016)
As the first organ in plants to sense water-deficit in the soil, roots have important roles for improving crop adaption to water limited environments. Stem water soluble carbohydrates (WSC) are a major carbon source for grain filling under drought conditions. The contributions of root WSC during grain filling under drought has not been revealed. Wheat parental lines of Westonia, Kauz and their derived four double haploid (DH) lines, namely, DH 125, DH 139, DH 307 and DH 338 were used in a field drought experiment with four replications. Through measurements of the root and stem WSC components, and the associated enzyme activities during grain filling, we identified that the levels of root WSC and fructan were one third of the levels in stems. In particular, root glucose and 6-kestose levels were one third of the stem, while the root fructose and bifurcose level were almost half of the stem and sucrose level was two third of the stem. The accumulation and the degradation patterns of root fructan levels were similar to that in the stem, especially under drought. Correlations between root fructan levels and grain assimilation were highly significant, indicating that under terminal drought, root WSC represents a redistributed carbon source for grain filling rather than deep rooting. The significantly higher root sucrose levels under drought suggest that sucrose may act as a signal under drought stress. As compared with stem fructose levels, the earlier increased root fructose levels in DH 307, DH 139 and DH 338 provided agile response to drought stress. Our root results further confirmed that β-(2-6) linkages predominate in wheat with patterns of 6-kestose being closely correlated with overall fructan patterns. Further research will focus on the roles of 6-FEH during fructan remobilization in stems.